Iron deficiency in patients with cardiogenic shock: protocol for a scoping review - Sascha Ott; Alexander Meyer; Lorenzo Germinario; Yassine Ghamri; Benjamin O’Brien; Daniel Catena; Tobias Roeschl; Felix Schoenrath (BMJ Open)
Introduction Cardiogenic shock (CS) is a severe condition characterised by low cardiac output and often hypotension, which results in organ hypoperfusion due to cardiac failure. As a form of acute heart failure, this condition seems to share similar underlying pathological mechanisms. It is well established that iron deficiency is correlated with chronic and acute heart failure, causing worsening of the symptoms, reduction of quality of life and survival and simultaneously increasing the rehospitalisation rates for all causes in these patients. It remains unclear whether there is an association between iron deficiency and CS. The objective of this scoping review will be to determine the actual state of the art regarding the significance of iron deficiency in patients affected by CS.Methods and analysis We will conduct a systematic review of the literature using MEDLINE and EMBASE via ‘Ovid’ (Elsevier) and Web of Science (2024 Clarivate). The goal is to analyse the incidence and clinical significance of iron deficiency in patients affected by cardiogenic shock. To gain a deeper insight into the underlying pathophysiological mechanisms, the review will include basic research conducted on both human subjects and on animal models as well as observational, randomised controlled studies and systematic reviews and meta-analysis. To maximise the identification of relevant reports and reduce loss of information, a systematic search of the literature will be performed from inception until January 2025 using the terms “iron deficiency” as well as “iron”, “ferritin”, “transferrin”, “transferrin saturation”, “hepcidin” and “soluble transferrin receptor” matching these terms with the keywords “cardiogenic shock”, “acute heart failure”, “advanced heart failure”, “decompensated heart failure”, “lvad”, “left ventricular assist device”, “mechanical circulatory support”, “VA-ECMO” and “Extracorporeal Life Support”. We will also use the corresponding MeSH and Emtree terms. In order to find grey literature, we will use the OADT.org internet-based database.Ethics and dissemination No additional ethics approval is required, as this review is based on existing research without new data collection. Only studies with ethics approval will be included. We plan to publish our findings in a peer-reviewed journal and present them at international conferences on cardiology, intensive and acute cardiovascular care, cardiac surgery and cardioanaesthesiology.